2023
DOI: 10.1111/aogs.14555
|View full text |Cite
|
Sign up to set email alerts
|

Risk of obstetric and perinatal complications in women presenting with breast cancer during pregnancy and the first year postpartum in Sweden 1973–2017: A population‐based matched study

Abstract: IntroductionFor women presenting with breast cancer during pregnancy, treatment guidelines were historically restricted to only surgical treatment. Over the past decades, chemotherapy administered during pregnancy has been gradually introduced. Although breast cancer treatments during ongoing pregnancy have been deemed safe, detailed information on potential obstetric risks is lacking. We aimed to assess the risk of adverse obstetric and perinatal outcomes of breast cancer in pregnancy and within 1 year postpa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 31 publications
(112 reference statements)
0
1
0
Order By: Relevance
“…Studies conducted in the previous decade have reported an increased risk for induced abortion, stillbirth, preterm birth, growth restrictions, neonatal intensive care unit admission, and neonatal death in pregnancies complicated by cancer. 4 , 6 , 32 , 33 One recent large study showed that cancer in pregnancy is associated with increased risk of induced abortion and planned premature birth. The researchers found that cancer during pregnancy was associated with increased neonatal morbidity and mortality, but mostly as a consequence of the increased frequency of prematurity in the group of exposed children.…”
Section: Discussionmentioning
confidence: 99%
“…Studies conducted in the previous decade have reported an increased risk for induced abortion, stillbirth, preterm birth, growth restrictions, neonatal intensive care unit admission, and neonatal death in pregnancies complicated by cancer. 4 , 6 , 32 , 33 One recent large study showed that cancer in pregnancy is associated with increased risk of induced abortion and planned premature birth. The researchers found that cancer during pregnancy was associated with increased neonatal morbidity and mortality, but mostly as a consequence of the increased frequency of prematurity in the group of exposed children.…”
Section: Discussionmentioning
confidence: 99%